Growth and wool production of sheep reared at highland of Nepal (Bangladesh Journal of Animal Science, 2018)
Sheep farmers lived in high altitude of Nepal have limited options of supplying roughages in winter season which is resulting severe feed deficit in these periods. Quality roughages like hay and other dried cereal stalks are not sufficiently available in the areas to mitigate the feed deficit in dry harsh winter. Therefore, the study was conducted to evaluate the effects of commonly practiced feeding system on growth and wool production of sheep in winter season. The research was performed at Sheep and Goat Research farm, Jumla, Nepal which is located at 2700 meters above sea level. The animals were supplied with three different rations viz (i) adlibitum oat hay with concentrate feed @ 1% of body weight;(ii) adlibitum conventional hay with concentrate feed @1% of body weight, and (iii) grazing in moderate pasture with concentrate feed @ 1% of body weight. The differences among the treatments were found significant ((p0.05) among the treatments. The treatment of feeding oat hay with concentrate @ 1% of body weight had yielded highest body weight gain.  The result of the study revealed that feeding oat hay was more profitable in comparison to conventional system of grazing and feeding conventional hay. Inclusion of oat hay on the sheep diet in dry harsh winter season could make substantial improvement in the body weight gain of the sheep in the high altitude of Nepal.Bang. J. Anim. Sci. 2017. 46 (3): 159-163